KEEFEKTIFAN PANDUAN PELATIHAN BERBASIS APPRECIATIVE INQUIRY TERHADAP PENINGKATAN KEMATANGAN KARIER SISWA SMP - Foctanian Lohmay; Triyono Triyono; M. Ramli (Pascasarjana Universitas Negeri Malang, 2017)
Career marturity is the ability of individuals to access, direct yourself based career information to make a choice in looking at opportunities that allow it to take decisions realistically. Career marturity of students with the skills of the teacher in facilitating the development of students. Teacher as facilitator required to have professional competence. Through the professional competence of teachers are required to master the substance of the materials provided to the students. But in fact teh observation og interviews with teachers BK junior high school in Kupang, the teacher is less skilled in facilitating the students in improving career marturity. Factors such low competence is part of the goverment, especially through the education department MGBK that have not facilitate teachers through training to the career marturity  of students with a training manual. A training manual was development to facilitate all teachers BK in Kupang city, in facilitating students to select and prepare for a career based on talents and interest of students. This training guide was developed using a model adapted the Brog and Gall with just nine steps. Free training is developed to enhance students' career marturity based appreciative inquirry is expected to boost competence BK teacher in improving students career marturity. The result showed that the percentage of data obtained from the assesment of expert BK 79% (decent) and expert media 81% (very decent). Individual test results for 89% (very worthy), based on those results the percentage per component in the asessment guide, described of follows: 86.3% of  the manual aspects, aspect of systematics 86%, 94.5% aspects us of language and aspects of the layout 90.5% then the results of the assesment in the guide concluded feasible to implement. The effectiveness of the training given tp students to measure the career marturity based appreciative inquiry is an excellent product and effectively to improve students career marturity. Suggestion put forward with regard to the further development, the training guide can intregrationwith othe competencies related to the student's career, for example design, decission-making  studied more in depth so as to produce products that are related to the whole students career marturity. Kematangan karier merupakan kemampuan individu dalam mengakses, mengarahkan diri berdasarkan informasi karier untuk membuat pilihan dalam melihat peluang yang memungkinkan untuk mengambil keputusan secara realistis. Berdasarkan observasi dan hasil wawancara menunjukkan bahwa kurang terampilnya guru dalam memfasilitasi siswa dalam meningkatkan kematangan karier siswa. Faktor rendahnya kompetensi tersebut ialah pihak pemerintah khususnya dinas pendidikan melalui MGBK yang belum memfasilitasi guru melalui pelatihan peningkatan kematangan karier siswa dengan panduan pelatihan. Panduan pelatihan dikembangkan dapat memfasilitasi guru BK se-Kota Kupang dalam memfasilitasi siswa untuk memilih dan mempersiapkan karier berdasarkan bakat dan minat siswa. Panduan pelatihan ini dikembangkan menggunakan model Borg dan Gall dengan mengadaptasi hanya sembilan langkah. Panduan pelatihan yang dikembangkan untuk meningkatkan kematangan karier siswa berbasis appreciative inquiry diharapkan dapat meningkatkan kompetessi guru BK dalam meningkatkan kematangan karier siswa. Hasil penelitian menunjukan data persentase yang diperoleh dari penilaian ahli BK 79% (layak) dan ahli media 81% (sangat layak). Hasil uji perorangan 89% (sangat layak). Efektivitas pelatihan diberikan kepada siswa untuk mengukur tingkat kematangan kariernya meningkat atau tidak, berdasarkan hasil uji Paired Samples t Test menunjukan hasil peningkatannya 59,24%. Simpulannya, panduan pelatihan peningkatan kematangan karier siswa berbasis appreciative inquiry adalah produk yang sangat baik dan efektif untuk meningkatkan kematangan karier siswa. Saran yang diajukan berkaitan dengan pengembangan selanjutnya, yakni panduan pelatihan dapat diintegritaskan dengan kompetensi lain yang berkaitan dengan karier siswa.